2016
DOI: 10.1080/00016357.2016.1206211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of audiovisual distraction on children’s behaviour during dental treatment: a randomized controlled clinical trial

Abstract: Aim: Dental anxiety leads to undesirable distresses such as avoidance of dental treatment and increase stress among caregivers that consequently affect the treatment quality. The aim of this study was therefore to evaluate the effectiveness of viewing videotaped cartoons using an eyeglass system (i-theatre™) as an audiovisual (AV) distraction technique on behaviour and anxiety in children receiving dental restorative treatment. Methods: Fifty-six consecutive children patients who presented for treatment and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
141
2
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(172 citation statements)
references
References 29 publications
14
141
2
15
Order By: Relevance
“…In line with the present study Morris et al concluded that by diverting the attention from an unpleasant medical setting to a pleasant and absorbing virtual world, virtual reality can markedly diminish patient's subjective pain experience. [28] In the recent studies conducted by Asvanund et al, [29] Khotana et-al, [8] Fakhurdin et-al and Hoge et al, [1,6] the results are corresponding to the current study where a significant reduction in anxiety and positive behaviour was instilled via the videoeyeglass in pediatric dental patients. Moreover in the present study, sedated children with N2O/O2 showed reduction in anxiety as depicted by pulse rate and Venham's anxiety scores.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In line with the present study Morris et al concluded that by diverting the attention from an unpleasant medical setting to a pleasant and absorbing virtual world, virtual reality can markedly diminish patient's subjective pain experience. [28] In the recent studies conducted by Asvanund et al, [29] Khotana et-al, [8] Fakhurdin et-al and Hoge et al, [1,6] the results are corresponding to the current study where a significant reduction in anxiety and positive behaviour was instilled via the videoeyeglass in pediatric dental patients. Moreover in the present study, sedated children with N2O/O2 showed reduction in anxiety as depicted by pulse rate and Venham's anxiety scores.…”
Section: Discussionsupporting
confidence: 57%
“…Younger children exhibit a higher level of fear and anxiety than the older children, and the distraction technique is helpful in those children who have low level of dental fear. [8] For this reason age group of 6-12 years was selected. All children were chosen with no past dental history as negative experience of the previous visit may lead to dental anxiety and fear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of behavioral interventions have been designed to reduce anxiety in children caused by dental procedures, such as the provision of information, live and filmed modeling, reinforcement of appropriate behavior, desensitization, tell-show-do, and many more [7]. The use of psychobehavioral approaches in medical and dental treatment situations is defined as a non-aversive approach aimed at modifying a child's discomfort by averting his or her attention away from the main task to accomplish successful treatment [1]. Intervention includes the provision of information; thus, giving information as a means of dental health education for children and doing so in a tell-show-do manner is likely to be more interesting for children.…”
Section: Introductionmentioning
confidence: 99%
“…Dental anxiety leads to undesirable distresses, such as avoidance of dental treatment, and tends to increase stress among caregivers, consequently affecting treatment quality [1]. Anxiety is an unpleasant inner emotional state characterized by uncertainty from the anticipation of a threatening event or situation [2].…”
Section: Introductionmentioning
confidence: 99%